THE CONVERGENCE OF ‘ÂDAT AND ISLAMIC LAW: The Practice of Gala in Aceh - Fauzi, Fauzi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: This article attempts to explain the position of the practice of gala in Acehnese society perspective in light of ‘âdat and Islamic law perspective. Theories of ‘âdat show that there are some pillars of gala that should be fulfilled; contract is done in front of chief of village and other village figures additional witnesses. Soon after the debt payment, murtahin (mortgager) must return the mortgaged to râhin (mortgagee) as the local saying goes “ngui pulang utang bayeu” means after use, the goods returned, the debt must be paid. In addition, marhûn cannot be exploited by murtahin as it is solely as security of the debt. These requirements have drawn closer to the Islamic law especially Syâfi‘î’s school. Research showed that the practice of gala (mortgage) in Aceh has contradicted the ‘âdat (customary law) and Islamic law in several points.Keywords: gala, marhûn, ‘âdat, Islamic law, Aceh